Microwave Assisted Cu‐Mediated Trifluoromethylation of Pyrimidine Nucleosides. Issue 12 (22nd December 2021) - Mangla, Priyanka; Sanghvi, Yogesh S.; Prasad, Ashok K.
Abstract: Trifluoromethylated nucleosides, such as trifluridine, have widespread applications in pharmaceuticals as anticancer and antiviral agents. However, site‐selective addition of a trifluoromethyl group onto a nucleobase typically requires either inconvenient multi‐step synthesis or expensive trifluoromethylation reagents, or results in low yield. This article describes a simple, scalable, and high‐yielding protocol for late‐stage direct trifluoromethylation of pyrimidine nucleosides via a microwave‐irradiated pathway. First, 5‐iodo pyrimidine nucleosides undergo complete benzoylation to obtain N 3 ‐benzoyl‐3', 5'‐di‐ O ‐benzoyl‐5‐iodo‐pyrimidine nucleosides as key precursors. Next, trifluoromethylation is carried out under both conventional and microwave heating using an inexpensive and commercially accessible Chen's reagent, i.e., methyl fluorosulfonyldifluoroacetate, to produce N 3 ‐benzoyl‐3', 5'‐di‐ O benzoyl‐5‐trifluoromethyl‐pyrimidine nucleosides. The microwave‐assisted transformation accentuates its simplicity, mild reaction conditions, and dominance, providing a facile route to access trifluoromethylation. Finally, the envisioned 5‐trifluoromethyl pyrimidine nucleosides are obtained by a routine debenzoylation procedure. This concludes a convenient three‐step synthesis to obtain trifluridine and its 2'‐modified analogs on a gram scale with consistently high yields, starting from their respective iodo‐precursors, and requires only one chromatographic purification at the trifluoromethylation step. Furthermore, this operationally simple protocol can be utilized as a definitive methodology to produce various other trifluoromethylated therapeutics. © 2021 Wiley Periodicals LLC. Basic Protocol : Synthesis of 5‐trifluoromethyl pyrimidine nucleosides 4a‐c Alternate Protocol : Conventional trifluoromethylation: Synthesis of N3‐benzoyl‐3', 5'‐di‐ O ‐benzoyl‐5‐trifluoromethyl pyrimidine nucleosides (3a ‐c )